Synthesis of Thin Films on Flexible Substrates: A Review - Ho, Soon Min (IDOSI Publications, 2016)
Preparation and characterization of thin films have been successfully deposited on various types of substrates including rigid substrate and flexible substrates. In this work, flexible substrates such as cloth, viewfoils, threads, titanium foil, molybdenum foil, polycarbonate, polyethylene terephthalate, polyimide and plastic foilwill be discussed as reported by many researchers. The spin coated CdTe films prepared on to polyimide substrate show an efficiency of 11 % under AM 1.5 illuminations. The obtained experimental results support that these films could be used in solar cell application.